Differential Immunogenicity and Protective Efficacy Elicited by MTO- and DMT-Adjuvanted CMFO Subunit Vaccines against Mycobacterium tuberculosis Infection. (4th September 2020) - Ullah, Nadeem; Hao, Ling; Wu, Yaqi; Zhang, Yandi; Lei, Qing; Banga Ndzouboukou, Jo-Lewis; Lin, Xiaosong; Fan, Xionglin
Abstract : Tuberculosis (TB) remains a major and global problem of public health. An effective TB subunit vaccine is urgently needed. Proper selection of the delivery system for the vaccine is crucial for inducing an appropriate immune response tailored to control the target pathogen. In this study, we compared the immunogenicity and protective efficacy of CMFO subunit vaccines against primary progressive TB in two different adjuvant systems: the MTO oil-in-water (O/W) emulsion composed of monophosphoryl lipid A (MPL), trehalose-6, 60-dibehenate (TDB), and oil in water emulsion MF59 and the DMT liposome containing dimethyldioctadecylammonium bromide (DDA), monophosphoryl lipid A (MPL), and trehalose-6, 60-dibehenate (TDB). Our results demonstrated that the DMT-adjuvanted CMFO could confer more significant protection against M. tuberculosis infection than the CMFO/MTO did in mice. In particular, the adjuvant DMT showed a stronger ability than the O/W emulsion to adjuvant CMFO subunit vaccine and enhanced protection, attributed to elicit Th1-biased responses, strong Th1/Th17 cytokine responses, and IFN- γ + or IL-2 + T cell responses. Therefore, our findings demonstrate that the liposome delivery system shows more effectiveness to adjuvant TB subunit vaccine than O/W emulsion and highlight the importance of adjuvant formulation for the better efficacy of a protein vaccine.